The Influence of Behavioral Skills and Instructional Challenges on Teaching Performance of Public Elementary Teachers - Telan, Jemerlyn L.; Andal, dilberto Z. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The primary objective of this study was to assess the level of teaching performance among public elementary school teachers in Magdalena District, Division of Laguna. Specifically, the study aimed to evaluate the teachers' behavioral skills and identify instructional challenges that may impact their performance. The findings of this research are intended to serve as the foundation for developing targeted intervention programs aimed at enhancing teacher effectiveness and promoting the delivery of quality education. A descriptive research design was employed, utilizing survey questionnaires, interviews, and classroom observations to gather data. A total of 100 public elementary school teachers from the Magdalena Sub-Office were selected as respondents.The results revealed significant positive relationships among behavioral skills, instructional challenges, and various dimensions of teaching performance. Notably, competencies such as effective communication, conflict resolution, and content delivery emerged as the most influential predictors of successful teaching outcomes. These findings underscore the importance of ongoing professional development focused on behavioral and instructional competencies. Furthermore, addressing issues related to resource availability and embracing classroom diversity were identified as critical factors in enhancing teaching performance. Overall, the study highlights the necessity for a comprehensive, skill-based approach to teacher development in order to foster a more effective and enriching educational environment.